2010
DOI: 10.5194/acp-10-7723-2010
|View full text |Cite
|
Sign up to set email alerts
|

GOMOS O<sub>3</sub>, NO<sub>2</sub>, and NO<sub>3</sub> observations in 2002–2008

Abstract: Abstract. The Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument onboard the European Space Agency's ENVISAT satellite measures ozone, NO 2 , NO 3 , H 2 O, O 2 , and aerosols using the stellar occultation method. Global coverage, good vertical resolution and the self-calibrating measurement method make GOMOS observations a promising data set for building various climatologies and time series. In this paper we present GOMOS nighttime measurements of ozone, NO 2 , and NO 3 during six years [2002]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 38 publications
6
49
0
Order By: Relevance
“…Stratospheric aerosol exerts a negative radiative forcing on the troposphere because it reduces solar radiation reaching the surface and the lower atmosphere. In addition, changes in diffuse light fraction have shown their 25 potential to enhance photosynthesis (Gu et al, 2003). The present study contributes to the SPARC/SSIRC initiative (Stratosphere-troposphere Processes And their Role in Climate/ Stratospheric Sulfur and Its Role in Climate).…”
Section: Introductionmentioning
confidence: 90%
“…Stratospheric aerosol exerts a negative radiative forcing on the troposphere because it reduces solar radiation reaching the surface and the lower atmosphere. In addition, changes in diffuse light fraction have shown their 25 potential to enhance photosynthesis (Gu et al, 2003). The present study contributes to the SPARC/SSIRC initiative (Stratosphere-troposphere Processes And their Role in Climate/ Stratospheric Sulfur and Its Role in Climate).…”
Section: Introductionmentioning
confidence: 90%
“…A persistent MSAO was observed in the nighttime O 3 density by Kyrölä et al (2010) using the GOMOS instrument on the Envisat satellite. The multi-year observations, extending from 2002 through 2008, exhibit a dominant semi-annual component at 90 km at the Equator (Fig.…”
Section: Msao -Model Versus Observationsmentioning
confidence: 99%
“…Both of these O studies also showed diurnal variations. The semi-annual oscillation at higher latitudes, not the focus of the current study, transitions into an annual oscillation (Thomas, 1990;Kyrölä et al, 2010).…”
Section: R L Gattinger Et Al: the Roles Of Vertical Advection And mentioning
confidence: 99%
See 2 more Smart Citations